The Influence of Parking Careers and Parking Facilities on User Satisfaction of Car Parking on Ngurah Rai Street Gianyar City - Ida Bagus Wirahaji; I Ketut Sutapa (Unit Publikasi Ilmiah, P3M, Politeknik Negeri Bali, 2021)
Driver satisfaction in making a trip is influenced by the quality of parking services. The purpose of this study was to analyze the effect of parking attendants and parking facilities on the satisfaction of car park users on Jalan Ngurah Rai, in Gianyar City, which is currently working on revitalizing traditional markets with modern concepts. Research using survey methods, distributing questionnaires to obtain 100 sheets of parking service user perception data. The results of the analysis show that the regression equation obtained is Y = 2.354 + 0.281 X1 + 0.672 X2. The parking attendant and parking facilities variables both partially and simultaneously have a significant positive effect on the user satisfaction variable. Value of Sig. variable parking attendant and parking facilities respectively 0.000 < 0.05. The value of tcount for parking attendants and parking facilities are 9,500 and 20.921, respectively > ttable = 1.9872. Fcount = 312.296 > 0.025324. The ability of the parking attendant and parking facilities variable in influencing the user satisfaction variable is quite large, as indicated by the coefficient value. determination (R2) of 86.3%.